Development and Validation of an Instrument Measuring Cyberbullying Among Malaysian Youths - Akmar Hayati, Ahmad Ghazali; Asnarulkhadi, Abu Samah; Siti Zobidah, Omar; Haslinda, Abdullah; Aminah, Ahmad; Hayrol Azril, Mohamed Shaffril (UNIMAS Publisher, 2019)
This study sought to develop and validate an instrument measuring cyberbullying among Malaysian youths. Exploratory factor analysis (EFA) was employed to determine the best sub-factors and items for the instrument, while confirmatory factor analysis (CFA) was performed to test and validate the measurement model. Results from EFA on 38 items showed that the items were pooled into four sub-factors. Meanwhile, results from CFA indicated that eight items had to be discarded in order to confirm that the model was fit. Overall, the final version of the instrument consisted of four cyberbullying sub-factors, namely, impersonation (13 items), cyberstalking and harassment (nine items), flaming (four items), and elimination (four items).